Financial stability and environment degradation in Turkey: evidence from fourier ARDL approach - Topalcık, Olgun; Kirikkaleli, Dervis (Frontiers in Environmental Science, 2024)
This study investigates the impact of financial stability on environmental degradation in Turkey, controlling for economic growth, renewable energy consumption, and primary energy consumption between 1990 and 2019. The study employs various statistical methodologies, including LS Unit Root, Fourier ARDL, DOLS, and FMOLS tests. The findings reveal an inverse relationship between financial stability and environmental degradation. Both economic growth and primary energy consumption are found to exacerbate environmental degradation. This study recommends that policymakers incorporate financial stability into policies aimed at reducing CO2 emissions. Furthermore, it emphasizes the importance of investing in renewable energy infrastructure and the transportation sector to effectively mitigate environmental degradation.